Development of rural tourism in the municipality of Dragash - Islami, Esad; Sejdiu, Lulzim (Technium Social Sciences Journal, 2021)
Tourism as an economic activity is a multidimensional phenomenon and is characterized by a pronounced mass in the global school. Modern working conditions in a field and tourist characteristic are characterized by a strong competition. Using tracking and research, we should not achieve a more effective analysis and assessment of natural potentials, anthropogenic resources, infrastructure and investments in the areas of Opolje and Gora, and beyond. With this paper we want to highlight the potentials and achievements of rural tourism in the municipality of Dragash, as well as in the use of policies and the use of concrete initiatives to make a unit. In this way it is necessary to know the tourism and rural economic market, as well as the opportunities for placing goods and the tourist offer of goods in that market, and thus provide reasonable examples for other municipalities in Kosovo.